A low dielectric constant borate composite microwave dielectric ceramic and cold sintering preparation method thereof
The preparation of borate composite microwave dielectric ceramics through low-temperature cold sintering process solves the problems of volatile elements loss and impurities introduction in traditional high-temperature processes, and realizes microwave dielectric ceramics with low dielectric constant and high quality factors, suitable for 5G communication technology demand.
Patent Information
- Application Number
- CN202410630585.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-21
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-05-21
AI Technical Summary
When preparing borate microwave dielectric ceramics in traditional high-temperature solid-phase reactions, it is easy to cause the loss of volatile elements and the introduction of second phase impurities, hindering the further application of materials and increasing manufacturing costs and carbon emissions.
Low-temperature cold sintering process is adopted to prepare low-dielectric constant borate composite microwave dielectric ceramics by pre-firing the boron source with calcium carbonate and strontium carbonate and mixing it with boron oxide solution respectively, and cold sintering is carried out to prepare low-dielectric constant borate composite microwave dielectric ceramics, controlling the sintering temperature and pressure to avoid volatility. Loss of sexual elements and improves density.
Microwave dielectric ceramics with low dielectric constant and high quality factor are achieved, reducing dielectric constant and improving quality factor, suitable for the needs of advanced wireless communication technologies, while reducing preparation costs and carbon emissions.
Smart Images

Figure CN118580057B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of microwave dielectric ceramics, and in particular to a low dielectric constant borate composite microwave dielectric ceramic and a cold sintering preparation method thereof. Background Art
[0002] With the rapid development of modern communication technology, dielectric materials have become indispensable materials for the research and utilization of functional materials. Among them, microwave dielectric ceramics (MWDCs) are key materials and are often used as electronic components and devices such as variable capacitors, filters, ceramic resonators, and microwave antennas. In order to meet the requirements of modern communications, especially 5G technology, electronic components and equipment must be integrated and miniaturized. Accordingly, microwave dielectric ceramics must not only have a high quality factor (Q×f), a low dielectric constant (ε r ), adjustable resonant frequency temperature coefficient (τ f ), and it should have the characteristics of small size, simple preparation process and low cost.
[0003] Borate ceramics have excellent dielectric properties, such as low dielectric constant and high quality factor, making them ideal candidate materials for 5G communication applications. The traditional method of preparing borate microwave dielectric ceramics is mainly to obtain pure phase borate ceramics by high temperature solid phase reaction. However, at high temperatures (1200-1500°C), the decomposition and evaporation of borates always lead to the loss of volatile elements or the introduction of second phase impurities, which seriously hinders the further application of borate microwave dielectric ceramics and increases carbon emissions and manufacturing costs.
[0004] The cold sintering process (CSP) is a new technology for achieving ceramic densification at low temperature. It is a new process for quickly densifying ceramic powder mixed with solvent (water or volatile solution) by uniaxial pressure and low temperature (<350°C). The CSP process has the characteristics of low sintering temperature, low energy consumption and relatively simple preparation requirements. Secondly, the CSP process cold sintering process can inhibit the abnormal growth of grains during ceramic sintering; effectively prevent the loss of volatile elements during sintering; better control the shrinkage rate during ceramic densification; and easily prepare high-precision ceramic components. Chinese patent CN 202310171449.3 discloses a low dielectric constant borate microwave dielectric ceramic and its cold sintering preparation method. The borate microwave dielectric ceramic is prepared by the cold sintering process (CSP), wherein the dielectric constant of the borate microwave dielectric ceramic is 4.42~6.88 and the quality factor is 6737~15563GHz. However, in order to meet the higher requirements of advanced wireless communication technology, it is necessary to further improve the quality factor while maintaining the low dielectric constant of microwave dielectric ceramics. Summary of the invention
[0005] The purpose of the present invention is to provide a low dielectric constant borate composite microwave dielectric ceramic and a cold sintering preparation method thereof. The low dielectric constant borate composite microwave dielectric ceramic obtained by the preparation method provided by the present invention has a low dielectric constant and a high quality factor.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a cold sintering preparation method of a low dielectric constant borate composite microwave dielectric ceramic, comprising the following steps:
[0008] (1) After first mixing a boron source and calcium carbonate, pre-calcining is performed to obtain a pre-calcined material 1; the molar ratio of the boron source to the calcium carbonate is 1:(2.5-3);
[0009] (2) After the boron source and strontium carbonate are mixed for the second time, they are pre-fired to obtain a pre-fired material 2; the molar ratio of the boron source to the strontium carbonate is 1:(2.5-3);
[0010] (3) After the pre-burned material 1 obtained in step (1) and the pre-burned material 2 obtained in step (2) are mixed with the boron oxide solution for the third time, cold sintering is performed to obtain a low dielectric constant borate composite microwave dielectric ceramic; the mass of the pre-burned material 2 is 20 to 40% of the total mass of the pre-burned material 1 and the pre-burned material 2;
[0011] There is no order of precedence for step (1) and step (2).
[0012] Preferably, the boron source in step (1) and step (2) independently comprises boron oxide and / or boric acid.
[0013] Preferably, the first mixing in step (1) and the second mixing in step (2) are both performed by ball milling;
[0014] The rotation speed of the ball mill is independently 350-400 r / min, and the time of the ball mill is independently 6-10 h.
[0015] Preferably, the pre-firing temperatures in step (1) and step (2) are independently 900 to 1050° C., and the pre-firing holding time is independently 8 to 10 hours.
[0016] Preferably, the mass concentration of the boron oxide solution in step (3) is 2.5-3.8%;
[0017] Preferably, in the step (3), the mass ratio of the total mass of the pre-burned material 1 and the pre-burned material 2 to the boron oxide solution is (1-2):1.
[0018] Preferably, the pre-burnt materials 1 and 2 in step (3) are respectively and sequentially subjected to wet ball milling, drying and sieving before use.
[0019] Preferably, the cold sintering temperature in step (3) is 285-300° C., the cold sintering holding time is 20-30 min, and the cold sintering pressure is 100-800 MPa.
[0020] Preferably, after the cold sintering is completed, the method further comprises annealing the cold sintered product;
[0021] The annealing treatment is carried out at a temperature of 800 to 850° C. and a heat preservation time of 3 to 6 hours.
[0022] The present invention also provides a low dielectric constant borate composite microwave dielectric ceramic prepared by the preparation method described in the above technical scheme, characterized in that the chemical formula of the borate composite microwave dielectric ceramic is xSr3B2O6-(1-x)Ca3B2O6, wherein 0.20≤x≤0.40, and x is the relative mass fraction.
[0023] The invention provides a cold sintering preparation method of a low dielectric constant borate composite microwave dielectric ceramic, comprising the following steps: (1) first mixing a boron source and calcium carbonate, and then pre-sintering to obtain a pre-sintered material 1; the molar ratio of the boron source to the calcium carbonate is 1:(2.5-3); (2) second mixing a boron source and strontium carbonate, and then pre-sintering to obtain a pre-sintered material 2; the molar ratio of the boron source to the strontium carbonate is 1:(2.5-3); (3) thirdly mixing the pre-sintered material 1 obtained in step (1) and the pre-sintered material 2 obtained in step (2) with a boron oxide solution, and then cold sintering to obtain a low dielectric constant borate composite microwave dielectric ceramic; the mass of the pre-sintered material 2 is 20-40% of the total mass of the pre-sintered material 1 and the pre-sintered material 2; there is no order of the steps (1) and (2). The present invention uses calcium carbonate and strontium carbonate to mix with a boron source to prepare two pre-sintered materials respectively, and the two pre-sintered materials are compounded to prepare a borate composite microwave dielectric ceramic, which can reduce the dielectric constant of the calcium borate ceramic; the doping of strontium carbonate can reduce and refine the grain size of the calcium borate generated by the calcium carbonate and the boron source, make the microstructure more compact, and improve the quality factor of the composite microwave dielectric ceramic. The results of the embodiment show that the low dielectric constant borate composite microwave dielectric ceramic obtained by the preparation method provided by the present invention has a dielectric constant of 4.56 to 6.02; a quality factor of 12586 to 18425 GHz; a resonant frequency temperature coefficient of -60 to -45 ppm / °C, and has a low dielectric constant and a high quality factor. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 XRD spectra of borate microwave dielectric ceramics of Examples 1 to 5 and Comparative Examples 1 to 2 of the present invention;
[0025] Figure 2It is a crystal structure diagram of the borate composite microwave dielectric ceramic of Examples 1 to 5 of the present invention;
[0026] Figure 3 The microwave dielectric properties of the borate microwave dielectric ceramics of Examples 1 to 5 and Comparative Examples 1 to 2 of the present invention are shown in the graph;
[0027] Figure 4 These are scanning electron microscopy (SEM) images of the borate composite microwave dielectric ceramics of Examples 1 to 5 of the present invention. DETAILED DESCRIPTION
[0028] The present invention provides a cold sintering preparation method of a low dielectric constant borate composite microwave dielectric ceramic, comprising the following steps:
[0029] (1) After first mixing a boron source and calcium carbonate, pre-calcining is performed to obtain a pre-calcined material 1; the molar ratio of the boron source to the calcium carbonate is 1:(2.5-3);
[0030] (2) After the boron source and strontium carbonate are mixed for the second time, they are pre-fired to obtain a pre-fired material 2; the molar ratio of the boron source to the strontium carbonate is 1:(2.5-3);
[0031] (3) After the pre-burned material 1 obtained in step (1) and the pre-burned material 2 obtained in step (2) are mixed with the boron oxide solution for the third time, cold sintering is performed to obtain a low dielectric constant borate composite microwave dielectric ceramic; the mass of the pre-burned material 2 is 20 to 40% of the total mass of the pre-burned material 1 and the pre-burned material 2;
[0032] There is no order of precedence for step (1) and step (2).
[0033] In the present invention, the boron source and calcium carbonate are first mixed and then pre-burned to obtain a pre-burned material 1.
[0034] In the present invention, the boron source preferably includes boron oxide and / or boric acid; the purity of the boron oxide is preferably 98%.
[0035] In the present invention, the purity of the calcium carbonate is preferably 99%.
[0036] In the present invention, the molar ratio of the boron source to calcium carbonate is 1: (2.5-3), preferably 1: (2.8-3), and more preferably 1: 3. The present invention limits the molar ratio of the boron source to calcium carbonate to the above range to ensure the formation of Ca3(BO3)2.
[0037] In the present invention, the boron source and calcium carbonate are preferably dried before use. The present invention has no particular limitation on the drying process, and the process may be carried out using the process known to those skilled in the art.
[0038] In the present invention, the first mixing method is preferably ball milling; the rotation speed of the ball mill is preferably 350-400 r / min, more preferably 380-400 r / min; the time of the ball milling is preferably 6-10 h, more preferably 7-8 h.
[0039] In the present invention, the ball milling is preferably carried out in a ball mill; the ball milling method is preferably wet ball milling; the dispersion medium of the wet ball milling is preferably anhydrous ethanol; the grinding balls used in the wet ball milling are preferably zirconia balls; the diameter of the zirconia balls is preferably 1.4-1.6 mm. In the present invention, the total mass of the boron source and calcium carbonate, and the mass ratio of the zirconia balls to anhydrous ethanol are preferably 1:3:2.5. The present invention can ensure uniform mixing of the raw materials by limiting the parameters of the ball milling to the above range.
[0040] After the ball milling is completed, the slurry obtained by the ball milling is preferably dried and sieved in sequence.
[0041] In the present invention, the drying temperature is preferably 80° C. The present invention has no particular limitation on the drying time, and the slurry can be dried to a constant weight. In the present invention, the drying is preferably performed in an oven.
[0042] In the present invention, the mesh size of the sieve used for the screening is preferably 80 meshes. The present invention has no special limitation on the screening operation, and the screening operation can be performed by the operation well known to those skilled in the art.
[0043] In the present invention, the pre-firing temperature is preferably 900-1050°C, more preferably 950-1000°C, and further preferably 1000°C; the heating rate to the pre-firing temperature is preferably 3-5°C / min, more preferably 3-4°C / min; the pre-firing holding time is preferably 8-10h, more preferably 9-10h. The present invention does not specifically limit the pre-firing equipment, and the sintering equipment commonly used in the art can be used. The present invention can ensure the reaction by setting the pre-firing parameters within the above range to generate Ca3(BO3)2.
[0044] In the present invention, the boron source and strontium carbonate are mixed for the second time and then pre-fired to obtain a pre-fired material 2.
[0045] In the present invention, the boron source preferably includes boron oxide and / or boric acid; the purity of the boron oxide is preferably 98%.
[0046] In the present invention, the purity of the strontium carbonate is preferably 99%.
[0047] In the present invention, the molar ratio of the boron source to strontium carbonate is 1: (2.5-3), preferably 1: (2.8-3), and more preferably 1: 3. The present invention limits the molar ratio of the boron source to strontium carbonate to the above range to ensure the formation of Sr3(BO3)2.
[0048] In the present invention, the boron source and strontium carbonate are preferably dried before use. The present invention has no particular limitation on the drying process, and the process may be carried out using the process known to those skilled in the art.
[0049] In the present invention, the second mixing method and parameter range setting and the operation steps after the second mixing are the same as the first mixing and the operation steps after the first mixing, and will not be repeated here.
[0050] In the present invention, the pre-firing temperature is preferably 900-1050°C, more preferably 950-1000°C, and further preferably 950°C; the heating rate to the pre-firing temperature is preferably 3-5°C / min, more preferably 3-4°C / min; the pre-firing holding time is preferably 8-10h, more preferably 9-10h. The present invention does not specifically limit the pre-firing equipment, and the sintering equipment commonly used in the art can be used. The present invention can ensure the reaction by setting the pre-firing parameters within the above range to generate Sr3(BO3)2.
[0051] The present invention mixes the boron source with calcium carbonate and strontium carbonate respectively and then pre-burns them, thereby avoiding the generation of impurity phases.
[0052] After obtaining the pre-burned material 1 and the pre-burned material 2, the present invention thirdly mixes the pre-burned material 1 and the pre-burned material 2 with a boron oxide solution and then performs cold sintering to obtain a low dielectric constant borate composite microwave dielectric ceramic.
[0053] In the present invention, the mass of the pre-burned material 2 is 20-40%, preferably 25-35%, and more preferably 30% of the total mass of the pre-burned material 1 and the pre-burned material 2. The present invention limits the content of the pre-burned material 1 and the pre-burned material 2 to the above range, so that the composite microwave dielectric ceramic has a lower dielectric constant and a higher quality factor.
[0054] In the present invention, the pre-burned material 1 and the pre-burned material 2 are preferably respectively and sequentially subjected to wet ball milling, drying and sieving before use.
[0055] In the present invention, the wet ball milling, drying and screening are the same as the wet ball milling, drying and screening in the first mixing, and will not be described in detail here.
[0056] In the present invention, the mass concentration of the boron oxide solution is preferably 2.5-3.8%, more preferably 3.0-3.8%. In the present invention, the boron nitride solution is introduced into the liquid phase as a sintering aid for cold sintering. The present invention limits the mass concentration of the boron oxide solution to the above range to ensure the subsequent preparation of composite microwave dielectric ceramics.
[0057] In the present invention, the mass ratio of the total mass of the pre-sintered material 1 and the pre-sintered material 2 to the boron oxide solution is preferably (1-2): 1, and more preferably (1-1.5): 1. The present invention limits the mass ratio of the total mass of the pre-sintered material 1 and the pre-sintered material 2 to the boron oxide solution to the above range, which can improve the dielectric properties of the microwave dielectric ceramic.
[0058] In the present invention, the third mixing method is preferably grinding. The present invention has no special limitation on the grinding operation, and the grinding operation can be performed by an operation well known to those skilled in the art. In the present invention, the grinding is preferably performed in a mortar.
[0059] In the present invention, the temperature of the cold sintering is preferably 270-290°C, more preferably 275-280°C; the holding time of the cold sintering is preferably 20-30min, more preferably 22-30min, and further preferably 25-30min; the pressure of the cold sintering is preferably 100-800MPa, more preferably 300-800MPa, and further preferably 600-800MPa. In the present invention, the pre-sintered material preliminarily synthesizes the calcium borate / strontium borate crystal phase during the cold sintering process, and the cold sintering process causes the composite ceramic to generate a densified ceramic. In the present invention, setting the temperature, time and pressure of the cold sintering within the above range can further reduce the dielectric constant of the composite microwave dielectric ceramic and improve the quality factor.
[0060] In the present invention, the mixed slurry obtained by the third mixing is preferably placed in a mold, and the mold is placed in a hot press for cold sintering.
[0061] In the present invention, the mold is preferably a cylindrical mold. The present invention has no special limitation on the size of the mold, and any mold well known to those skilled in the art can be used.
[0062] After the cold sintering is completed, the present invention preferably further comprises annealing the material obtained by the cold sintering.
[0063] In the present invention, the temperature of the annealing treatment is preferably 800-850°C, more preferably 800-830°C; the holding time of the annealing treatment is preferably 3-6h, more preferably 5-6h; the annealing treatment is preferably carried out in an air atmosphere. The present invention limits the temperature and time of the annealing treatment to the above ranges to further improve the performance of the low dielectric constant borate composite microwave dielectric ceramic.
[0064] In the present invention, the cooling method of the annealing treatment is preferably natural cooling to room temperature.
[0065] After the annealing treatment is completed, the present invention preferably grinds and polishes the annealed product to obtain a low dielectric constant borate composite microwave dielectric ceramic. The present invention has no special limitation on the grinding and polishing operation, and can be performed using operations well known to those skilled in the art.
[0066] The invention adopts calcium carbonate and strontium carbonate to mix with a boron source to prepare two pre-sintered materials respectively, and the two pre-sintered materials are compounded to prepare borate composite microwave dielectric ceramics, which can reduce the dielectric constant of calcium borate ceramics; the doping of strontium carbonate can reduce and refine the grain size of calcium borate generated by calcium carbonate and the boron source, make the microstructure more compact, and improve the quality factor of the composite microwave dielectric ceramics.
[0067] The present invention also provides a low dielectric constant borate composite microwave dielectric ceramic prepared by the preparation method described in the above technical scheme, wherein the chemical formula of the borate composite microwave dielectric ceramic is xSr3B2O6-(1-x)Ca3B2O6, wherein 0.20≤x≤0.40, and x is the relative mass fraction.
[0068] The borate composite microwave dielectric ceramic provided by the invention has a dielectric constant of 4.56 to 6.02, a quality factor of 12586 to 18425 GHz, and a resonant frequency temperature coefficient of -60 to -45 ppm / °C.
[0069] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0070] Example 1
[0071] A cold sintering preparation method of low dielectric constant borate composite microwave dielectric ceramics, comprising the following steps:
[0072] (1) 0.2 mol B2O3 (purity of 98%) and 0.6 mol CaCO3 (purity of 99%) were dried separately, and then placed in a ball mill, and zirconium oxide balls (particle size of 1.4-1.6 mm) and anhydrous ethanol were added at the same time, and wet ball milling was performed at a speed of 400 r / min for 8 h; the obtained slurry was placed in an oven, dried to constant weight at 80°C, sieved through a sieve with an aperture of 80 mesh, and placed in a high-temperature sintering furnace, and heated to 1000°C at a heating rate of 3°C / min for pre-sintering, and the heat preservation time was 10 h to obtain pre-sintered material 1; the mass ratio of the total mass of B2O3 and CaCO3 to the mass of zirconium oxide balls and anhydrous ethanol was 1:3:2.5;
[0073] (2) 0.2 mol B2O3 (purity of 98%) and 0.6 mol SrCO3 (purity of 99%) were dried separately, and then placed in a ball mill, and zirconium oxide balls (particle size of 1.4-1.6 mm) and anhydrous ethanol were added, and wet ball milling was performed at a speed of 400 r / min for 8 h; the obtained slurry was placed in an oven, dried to constant weight at 80°C, sieved through a sieve with an aperture of 80 mesh, and placed in a high-temperature sintering furnace, and pre-fired at a heating rate of 3°C / min to 950°C, and the heat preservation time was 10 h to obtain pre-fired material 2; the mass ratio of the total mass of B2O3 and SrCO3 to the mass ratio of zirconium oxide balls and anhydrous ethanol was 1:3:2.5;
[0074] (3) The obtained pre-sintered materials 1 and 2 were placed in a ball mill with zirconium oxide balls (with a diameter of 1.4 to 1.6 mm) and anhydrous ethanol (wherein the mass ratio of pre-sintered material 1 / pre-sintered material 2, zirconium oxide balls and anhydrous ethanol was 1:3:2.5), and wet ball milled at a speed of 400 r / min for 8 h; the obtained slurry was placed in an oven, dried to constant weight at 80° C., and sieved through a sieve with an aperture of 80 mesh; a total mass of 4.5 g of pre-sintered materials 1 and 2 (the content of pre-sintered material 2 was 20% of the total mass of pre-sintered materials 1 and 2) was added to the pre-sintered materials 1 and 2. %) and 4.5g of a saturated boron oxide solution with a mass concentration of 3.8% are placed in a mortar, and after grinding and mixing evenly, the obtained slurry is poured into a cylindrical mold, and then the cylindrical mold is placed in a hot press, and cold sintering is carried out under the conditions of a pressure of 800Mpa and a temperature of 280℃ for 30min. The cold sintered product is annealed at 800℃ for 6h, and the borate composite microwave dielectric ceramic is obtained after grinding and polishing, which is recorded as xSr3B2O6-(1-x)Ca3B2O6 (x=0.20).
[0075] Example 2
[0076] The only difference between Example 2 and Example 1 is that the content of pre-burnt material 2 is 25% of the total mass of pre-burnt material 1 and pre-burnt material 2, and the obtained borate composite microwave dielectric ceramic is recorded as xSr3B2O6-(1-x)Ca3B2O6 (x=0.25).
[0077] Example 3
[0078] The only difference between Example 3 and Example 1 is that the content of pre-burnt material 2 is 30% of the total mass of pre-burnt material 1 and pre-burnt material 2, and the obtained borate composite microwave dielectric ceramic is recorded as xSr3B2O6-(1-x)Ca3B2O6 (x=0.30).
[0079] Example 4
[0080] The only difference between Example 4 and Example 1 is that the content of pre-burnt material 2 is 35% of the total mass of pre-burnt material 1 and pre-burnt material 2, and the obtained borate composite microwave dielectric ceramic is recorded as xSr3B2O6-(1-x)Ca3B2O6 (x=0.35).
[0081] Example 5
[0082] The only difference between Example 5 and Example 1 is that the content of pre-burnt material 2 is 40% of the total mass of pre-burnt material 1 and pre-burnt material 2, and the obtained borate composite microwave dielectric ceramic is recorded as xSr3B2O6-(1-x)Ca3B2O6 (x=0.40).
[0083] Comparative Example 1
[0084] The only difference between Comparative Example 1 and Example 1 is that pre-burned material 2 is not prepared, and only pre-burned material 1 is used to prepare borate microwave dielectric ceramics. The rest is the same as Example 1. The obtained borate microwave dielectric ceramics are recorded as Ca3B2O6 (x=0.00).
[0085] Comparative Example 2
[0086] The only difference between Comparative Example 2 and Example 1 is that pre-burned material 1 is not prepared, and only pre-burned material 2 is used to prepare borate microwave dielectric ceramics. The rest is the same as Example 1. The obtained borate microwave dielectric ceramics are recorded as Sr3B2O6 (x=1.00).
[0087] The microwave dielectric ceramics obtained in Examples 1 to 5 and Comparative Examples 1 to 2 were subjected to X-ray diffraction test, and the obtained XRD patterns are as follows: Figure 1 As shown, from Figure 1 It can be seen that the present invention successfully prepared xSr3B2O6-(1-x)Ca3B2O6 composite ceramics. With the increase of x content, the diffraction peak of strontium borate can be seen, and the height of the diffraction peak gradually increases with the change of x. Except for the diffraction peaks of calcium borate and strontium borate, no other impurities are generated, indicating that a composite ceramic is formed.
[0088] Figure 2 The crystal structure diagram of the borate composite microwave dielectric ceramic obtained in Examples 1 to 5 is shown in FIG. Figure 2 It can be seen that the crystal structures of calcium borate and strontium borate both belong to the trigonal system, R-3c (167) space group; the crystal structure is composed of [CaO6] / [SrO6] octahedra and [BO3] plane triangles (B is located in the center of the equilateral triangle composed of three oxygen atoms) in a layered structure; three adjacent [CaO6] / [SrO6] octahedra and one BO plane triangle form the first layer, five adjacent [CaO6] / [SrO6] octahedra and two BO plane triangles form the second layer, and three adjacent [CaO6] / [SrO6] octahedra and one BO plane triangle form the third layer. The two layers are connected by sharing oxygen atoms at the vertices, and the [CaO6] / [SrO6] octahedra between each layer are staggered and stacked.
[0089] The dielectric properties of the borate microwave dielectric ceramics obtained in Examples 1 to 5 and Comparative Examples 1 to 2 were tested, and the test results obtained are as follows: Figure 3 As shown in Table 1, ε r is the dielectric constant, Q×f is the quality factor, τ f is the resonant frequency temperature coefficient.
[0090] Table 1 Dielectric properties of borate microwave dielectric ceramics obtained in Examples 1 to 5 and Comparative Examples 1 to 2
[0091] Dielectric constant Quality factor / GHz <![CDATA[Temperature coefficient of resonant frequency / ppm·°C -1 > Example 1 6.02 18425 -60 Example 2 5.67 16258 -57 Example 3 5.24 14857 -52 Example 4 4.86 13562 -50 Example 5 4.56 12586 -47 Comparative Example 1 6.68 15862 -30 Comparative Example 2 4.23 13564 -48
[0092] from Figure 3 It can be concluded from Table 1 that with the increase of Sr doping amount, the dielectric constant of xSr3B2O6-(1-x)Ca3B2O6 ceramics gradually decreases and the temperature coefficient of resonant frequency gradually increases; by adding Sr, the dielectric constant of xSr3B2O6-(1-x)Ca3B2O6 can be made lower than that of Ca3B2O6, and a small amount of Sr can improve the quality factor of xSr3B2O6-(1-x)Ca3B2O6 ceramics.
[0093] The borate composite microwave dielectric ceramics obtained in Examples 1 to 5 were tested by scanning electron microscopy, and the obtained SEM images are as follows: Figure 4 As shown in the figure, with the increase of Sr doping amount, the ceramic grain boundary gradually becomes clear, the grains are obvious but the pores are reduced, resulting in increased ceramic density. When the Sr doping amount is x=0.40, the ceramic density is optimal.
[0094] The low dielectric constant borate composite microwave dielectric ceramic obtained by the preparation method provided by the invention has a dielectric constant of 4.56 to 6.02, a quality factor of 12586 to 18425 GHz, and a resonant frequency temperature coefficient of -60 to -45 ppm / °C, and has a low dielectric constant and a high quality factor.
[0095] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A cold sintering preparation method of a low dielectric constant borate composite microwave dielectric ceramic, comprising the following steps: (1) After first mixing the boron source and calcium carbonate, pre-calcining is performed to obtain a pre-calcined material 1; the molar ratio of the boron source to the calcium carbonate is 1:(2.5-3); (2) After the boron source and strontium carbonate are mixed for the second time, they are pre-calcined to obtain a pre-calcined material 2; the molar ratio of the boron source to the strontium carbonate is 1:(2.5-3); (3) After the pre-sintered material 1 obtained in step (1) and the pre-sintered material 2 obtained in step (2) are mixed with the boron oxide solution for the third time, cold sintering is performed to obtain a low dielectric constant borate composite microwave dielectric ceramic; the mass of the pre-sintered material 2 is 20-25% of the total mass of the pre-sintered material 1 and the pre-sintered material 2; There is no order of precedence between step (1) and step (2); The boron source in step (1) and step (2) independently comprises boron oxide and / or boric acid; The mass concentration of the boron oxide solution in step (3) is 2.5-3.8%; In the step (3), the mass ratio of the total mass of the pre-burned material 1 and the pre-burned material 2 to the boron oxide solution is (1-2):1; In the step (3), the cold sintering temperature is 270-290° C., the cold sintering holding time is 20-30 min, and the cold sintering pressure is 100-800 MPa; After the cold sintering is completed, the cold sintered product is annealed; The temperature of the annealing treatment is 800-850° C., and the holding time of the annealing treatment is 3-6 hours.
2. The preparation method according to claim 1, characterized in that: The first mixing in step (1) and the second mixing in step (2) are both performed by ball milling; The rotation speed of the ball mill is independently 350-400 r / min, and the time of the ball mill is independently 6-10 h.
3. The preparation method according to claim 1, characterized in that: The pre-firing temperatures in the steps (1) and (2) are independently 900-1050° C., and the pre-firing holding time is independently 8-10 hours.
4. The preparation method according to claim 1, characterized in that: In the step (3), the pre-burned material 1 and the pre-burned material 2 are respectively and sequentially subjected to wet ball milling, drying and sieving before use.
5. The low dielectric constant borate composite microwave dielectric ceramic prepared by the preparation method according to any one of claims 1 to 4, characterized in that: The chemical formula of the borate composite microwave dielectric ceramic is xSr3B2O 6- (1-x)Ca3B2O6, where 0.20≤x≤0.25, and x is the relative mass fraction.
Citation Information
Patent Citations
A low dielectric constant borate microwave dielectric ceramic and its cold sintering preparation method
CN116199498B
Two-phase composite microwave dielectric ceramic material as well as preparation method and application thereof
CN114573344A
Low-dielectric-constant borate microwave dielectric ceramic and cold sintering preparation method thereof
CN116199498A